κ-opioid receptor: from analgesic target to neuroimmune hub - Tan, Qinsi; Zheng, Mengjin; Xing, Huaixin (Frontiers in Pharmacology, 2026)
Originally characterized as a classical mediator of analgesia, the κ-opioid receptor (KOR) has recently emerged as a pivotal regulator at the crossroads of the nervous and immune systems. Beyond its canonical role in nociceptive processing, a growing body of evidence reveals that KOR exerts profound immunomodulatory effects. The receptor is broadly expressed across diverse immune cell populations, including macrophages, microglia, and lymphocytes, where it contributes to immune homeostasis by attenuating the activity of key pro-inflammatory transcription factors, notably nuclear factor κB (NF-κB) and signal transducer and activator of transcription 3 (STAT3). These regulatory effects are mediated through both canonical G protein–coupled (Gαi/o) pathways and non-canonical β-arrestin–dependent cascades. Preclinical investigations have demonstrated that pharmacological modulation of KOR confers significant therapeutic benefits in a range of immune-related disorders, including atopic dermatitis, multiple sclerosis, and osteoarthritis. However, the clinical translation of traditional KOR agonists remains limited by dose-dependent central nervous system (CNS) adverse effects, such as dysphoria and hallucinations. In this review, we synthesize recent advances in elucidating the molecular and cellular mechanisms underlying KOR-mediated immunoregulation, highlight its therapeutic potential across diverse neuroimmune pathologies, and discuss innovative pharmacological strategies, such as peripherally restricted and signaling-biased ligands-designed to preserve beneficial immunomodulatory and analgesic properties while minimizing CNS liabilities. Collectively, these insights redefine KOR as a central node in neuroimmune communication and point toward the development of next-generation precision therapeutics targeting this axis.